2017
DOI: 10.1115/1.4037743
|View full text |Cite
|
Sign up to set email alerts
|

Moving-Horizon Modulating Functions-Based Algorithm for Online Source Estimation in a First-Order Hyperbolic Partial Differential Equation

Abstract: In this paper, an online estimation algorithm of the source term in a first-order hyperbolic partial differential equation (PDE) is proposed. This equation describes heat transport dynamics in concentrated solar collectors where the source term represents the received energy. This energy depends on the solar irradiance intensity and the collector characteristics affected by the environmental changes. Control strategies are usually used to enhance the efficiency of heat production; however, these strategies oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…reduce the size of the linear system), and hence reduce the computational load. We propose to use Algorithm IV.1 for constructing modulating functions based 1 If a time-dependent modulating function is used, thenn in the algorithm refers to the temporal derivative's order.…”
Section: Proposed Selection Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…reduce the size of the linear system), and hence reduce the computational load. We propose to use Algorithm IV.1 for constructing modulating functions based 1 If a time-dependent modulating function is used, thenn in the algorithm refers to the temporal derivative's order.…”
Section: Proposed Selection Strategymentioning
confidence: 99%
“…Thus, solutions of these equations are usually approximated numerically, this increases the difficulty of solving estimation problems in DEs, especially in the case of higher-order nonlinear DEs. Modulating functions-based method (MFBM) is among the recent active and effective methods for real-time estimation of input, states, and parameters of systems governed by DEs [1]- [6]. The MFBM consists of a kernel-based linear integral operator in which the kernel is given by certain functions called modulating functions.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate F while the system is operating, a movinghorizon strategy is applied [38]. The main idea of this strategy is to implement the MFBM on a time window that moves one sampling time forward.…”
Section: B Modulating Function-based I-pid Controllermentioning
confidence: 99%
“…This offers the additional advantages of giving estimates after a fixed and predetermined amount of time, contrary to usual Kalman-based filtering methods. Originally proposed towards parameter estimation, the modulating function method was more recently extended to include state estimation [23] [19].Many studies considering the modulating function approach showed satisfactory performance, but mostly in simulations using artificial data [19] or sources generated from real profiles [5]. In contrast to that and to the best of our knowledge, not many applications can be found in the literature dealing with experiments done on actual measurements, to the notable exception of [11], where Hartley modulating functions are used to estimate the parameters of a thyristor driven DC-motor.…”
mentioning
confidence: 99%
“…Many studies considering the modulating function approach showed satisfactory performance, but mostly in simulations using artificial data [19] or sources generated from real profiles [5]. In contrast to that and to the best of our knowledge, not many applications can be found in the literature dealing with experiments done on actual measurements, to the notable exception of [11], where Hartley modulating functions are used to estimate the parameters of a thyristor driven DC-motor.…”
mentioning
confidence: 99%